Defect-engineered three-dimensional sodium-philic current collector and preparation method thereof, and negative electrode-free sodium battery

CN122907645APending Publication Date: 2026-10-13XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611127199.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

其一,本发明在导电金属基底表面原位构筑了分布有缺陷调控层的三维纳米结构层,缺陷调控层中的氧空位和低价态金属离子缺陷增强了集流体对钠离子的吸附与亲和作用,并提高了三维纳米结构层的载流子浓度和电子电导,使钠离子能够以较低的成核过电位在集流体表面均匀成核与沉积,抑制了钠枝晶和死钠的形成,提高了电池的库伦效率。氧空位作为富电子的活性位点能够与钠离子形成较强的化学吸附作用,为钠的形核提供了大量亲钠成核位点,从而显著降低了钠形核所需的能垒;低价态金属离子在禁带中引入浅施主能级,进一步提升了三维纳米结构层的电子电导,使沉积界面的电荷转移更为顺畅;二者协同作用使钠离子在集流体表面呈现低过电位、高密度且均匀的形核行为,从根本上抑制了因局部电流集中而诱发的枝晶生长与死钠累积。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907645A_ABST
    Figure CN122907645A_ABST
Patent Text Reader

Abstract

The application discloses a kind of defect engineering regulation's three-dimensional sodium affinity current collector and preparation method thereof, and no negative electrode sodium battery.The current collector includes electrically conductive metal substrate, three-dimensional nanostructure layer constructed in its surface in situ and defect regulation layer distributed in three-dimensional nanostructure layer, and defect regulation layer includes at least one of oxygen vacancy, low-valence metal ion defect and lattice defect.Its preparation method is: with electrically conductive metal substrate as anode in fluoride-containing organic electrolyte anodic oxidation forms three-dimensional nanotube array, with nanotube array as cathode carries out cathodic reduction and introduces defect, and then low-temperature heat treatment is carried out in protective atmosphere.Three-dimensional nanostructure layer provides abundant sodium affinity site and buffers sodium deposition volume change, and defect regulation layer improves current collector carrier concentration and sodium affinity, so that sodium ion is uniformly deposited with lower overpotential, sodium dendrite and dead sodium are inhibited, and used as negative electrode current collector can improve coulomb efficiency and cycle stability, and process is simple, easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a three-dimensional sodium-loving current collector with defect engineering control and its preparation method, and a sodium battery without a negative electrode. Background Technology

[0002] Sodium is abundant and inexpensive, making sodium-ion batteries a focus of attention in large-scale energy storage and other fields. Among various sodium-ion battery systems, the negative electrode-less sodium battery does not pre-load a negative electrode active material on the negative electrode side during assembly; only the negative electrode current collector is retained. During charging, sodium ions released from the positive electrode are directly reduced and deposited on the surface of the negative electrode current collector to form metallic sodium. During discharging, the metallic sodium dissolves again and returns to the positive electrode in the form of sodium ions. This configuration eliminates the need for a negative electrode active material and its carrier, significantly improving the battery's energy density and volumetric energy density while simplifying the battery manufacturing process.

[0003] However, the cycle performance and coulombic efficiency of anode-free sodium batteries largely depend on the deposition and dissolution behavior of sodium ions on the surface of the anode current collector. Currently, the widely used anode current collectors are mostly two-dimensional planar metal foils such as copper foil and aluminum foil. Their surfaces are relatively inert, and the active sites available for sodium nucleation are limited. When sodium ions are deposited on their surfaces, the nucleation overpotential is high, and the deposition distribution is uneven.

[0004] Uneven sodium deposition easily induces the growth of sodium dendrites. These dendrites can not only pierce the diaphragm, posing a safety hazard, but also break off during repeated charge-discharge cycles, forming dead sodium that loses electrical contact with the conductive network, resulting in irreversible loss of active sodium. Furthermore, metallic sodium undergoes significant volume changes during deposition and dissolution, making it difficult for two-dimensional planar current collectors to provide effective support and buffering space. This leads to easy peeling of the deposited layer, further exacerbating the rapid capacity decay and the decrease in coulombic efficiency.

[0005] To improve sodium deposition behavior, researchers have attempted to functionalize the current collector surface or construct three-dimensional structures, achieving some progress. However, these approaches often fail to simultaneously achieve high conductivity, high affinity for sodium, and three-dimensional buffering capacity against volume expansion. Furthermore, some solutions rely on complex processes such as magnetron sputtering and chemical vapor deposition, resulting in high manufacturing costs and hindering industrial application. Therefore, providing a sodium-ion battery current collector that combines good conductivity, excellent sodium affinity, and three-dimensional structural stability with a simple fabrication process remains a pressing technical challenge in this field. Summary of the Invention

[0006] In order to overcome the above shortcomings of the prior art, the purpose of the present invention is to provide a defect engineering regulated three-dimensional sodium-philic current collector, its preparation method, and an anode-free sodium battery. This current collector simultaneously has good electrical conductivity, excellent sodium affinity, and three-dimensional buffering capacity for the volume change of sodium deposition, thereby reducing the nucleation and deposition overpotential of sodium, promoting uniform sodium deposition, inhibiting the formation of sodium dendrites and dead sodium, improving the Coulombic efficiency and cycling stability of the battery, and featuring a simple preparation process that is easy for industrial promotion.

[0007] To achieve the above purpose, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a defect engineering regulated three-dimensional sodium-philic current collector, comprising a conductive metal substrate, a three-dimensional nanostructure layer in-situ constructed on the surface of the conductive metal substrate, and a defect regulation layer distributed in the three-dimensional nanostructure layer; the defect regulation layer includes at least one of oxygen vacancies, low-valence metal ion defects, or lattice defects.

[0008] Further, the conductive metal substrate is selected from one or more of titanium foil, nickel foil, aluminum foil and copper foil.

[0009] Further, the three-dimensional nanostructure layer is a nanotube array grown in-situ on the surface of the conductive metal substrate, and its material is selected from at least one of metal oxides, metal nitrides, metal oxynitrides and metal sulfides. On the one hand, the three-dimensional nanostructure layer provides a large number of active surfaces for sodium ion adsorption and nucleation, and on the other hand, its longitudinally penetrating nanotube gaps can accommodate metallic sodium during sodium deposition and buffer its volume expansion.

[0010] Further, the conductive metal substrate is a titanium foil, and the three-dimensional nanostructure layer is a nanotube array, wherein the nanotubes in the nanotube array have a tube length of 0.1 to 40 μm and a tube diameter of 10 to 1000 nm, and are arranged in an oriented manner along the surface of the substrate.

[0011] Further, the defect regulation layer includes oxygen vacancies and low-valence titanium ions, and the three-dimensional nanostructure layer has a non-stoichiometric structure, where 0<x<2, exhibiting n-type semiconductor characteristics. The introduction of oxygen vacancies and low-valence titanium ions in introduces donor energy levels into the band gap, increases the carrier concentration and electronic conductivity of the three-dimensional nanostructure layer, and enhances its adsorption effect on sodium ions, thereby reducing the nucleation overpotential of sodium and inducing uniform nucleation of sodium.

[0012] In a second aspect, the present invention provides a preparation method of the above three-dimensional sodium-philic current collector, comprising the following steps: S1. Using the conductive metal substrate as the anode and the inert electrode as the cathode, anodic oxidation is performed in an organic electrolyte containing fluoride to form a three-dimensional nanotube array as the three-dimensional nanostructure layer on the surface of the conductive metal substrate in situ. S2. Using a three-dimensional nanotube array as the cathode and an inert electrode as the anode, a cathode reduction treatment is performed in an electrolyte containing electrolyte to introduce oxygen vacancies and low-valence metal ion defects into the three-dimensional nanotube array, forming the defect control layer. S3. The product obtained in S2 is heat-treated under a protective atmosphere to obtain the defect-engineered three-dimensional sodium-loving current collector.

[0013] This invention prepares a three-dimensional sodium-loving current collector using a combination of anodic oxidation, cathodic reduction, and low-temperature heat treatment: anodic oxidation constructs a three-dimensional nanotube array in situ on the surface of a conductive metal substrate; cathodic reduction introduces oxygen vacancies and low-valence metal ion defects into the nanotube array electrochemically, achieving n-type self-doping; and low-temperature heat treatment stabilizes these defects without damaging the nanostructure, thus maintaining the current collector's conductivity and sodium affinity over a long period. This method is simple, operates under mild conditions, and is easily industrially applicable.

[0014] Further, the organic electrolyte in S1 comprises an organic solvent and a fluoride, wherein the organic solvent is selected from one or more of ethylene glycol, glycerol, and dimethyl sulfoxide, and the fluoride is selected from... One or more of NaF, KF, and LiF are present, and the concentration of the fluoride in the organic electrolyte is 0.05~1M; the organic electrolyte also contains 1~10mM of [a specific compound / component]. .

[0015] Furthermore, the anodizing temperature in S1 is 0~30℃, the voltage is 5~300V, and it is applied in a step-decreasing, linearly decreasing, or exponentially decreasing manner; the anodizing is a single anodizing or a double anodizing, wherein the double anodizing is performed after the nanotubes are formed by the first anodizing, the nanotube layer is removed by ultrasonication, and then a second anodizing is performed under the same conditions.

[0016] Furthermore, the electrolyte in S2 is a sodium sulfate solution, a sodium chloride solution, or the organic electrolyte described in S1; the current for the cathode reduction treatment is 1~100mA, and the time is 10min~2h.

[0017] Furthermore, the protective atmosphere in S3 is nitrogen or argon, and the heat treatment temperature is 250~500℃ and the time is 0.5~5h; the heat treatment temperature is 300~450℃ and the time is 1~3h.

[0018] Thirdly, the present invention provides a negative electrode-free sodium battery, comprising a positive electrode, a negative electrode current collector, an electrolyte, and a separator. The negative electrode current collector is the aforementioned three-dimensional sodium-loving current collector, and no pre-loaded negative electrode active material is disposed on the negative electrode current collector. In some embodiments, the positive electrode active material is sodium iron pyrophosphate; the electrolyte comprises a sodium salt and an ether solvent, wherein the sodium salt comprises... and The ether solvent includes ethylene glycol dimethyl ether; the separator is a ceramic-coated polypropylene separator.

[0019] Compared with the prior art, the present invention has the following beneficial effects: Firstly, this invention constructs a three-dimensional nanostructure layer with a defect-controlled layer distributed in situ on the surface of a conductive metal substrate. Oxygen vacancies and low-valence metal ion defects in the defect-controlled layer enhance the adsorption and affinity of sodium ions by the current collector, and increase the carrier concentration and electronic conductivity of the three-dimensional nanostructure layer. This allows sodium ions to nucleate and deposit uniformly on the current collector surface at a lower nucleation overpotential, suppressing the formation of sodium dendrites and dead sodium, and improving the coulombic efficiency of the battery. Oxygen vacancies, as electron-rich active sites, can form strong chemisorption with sodium ions, providing a large number of sodium-loving nucleation sites for sodium nucleation, thus significantly reducing the energy barrier required for sodium nucleation. Low-valence metal ions introduce shallow donor levels in the band gap, further enhancing the electronic conductivity of the three-dimensional nanostructure layer, making charge transfer at the deposition interface smoother. The synergistic effect of these two factors results in sodium ions exhibiting low overpotential, high-density, and uniform nucleation behavior on the current collector surface, fundamentally suppressing dendrite growth and dead sodium accumulation induced by localized current concentration.

[0020] Secondly, the vertically interconnected nanotube structure of the three-dimensional nanostructure provides a space and buffer zone for sodium deposition, which can buffer the volume changes of sodium during deposition and dissolution, suppress the peeling of the deposited layer, and improve the cycle stability of the battery. The vertically oriented and interconnected nanotube array has a large specific surface area, which can effectively reduce the local deposition current density and make the sodium ion flux uniformly distributed on the current collector surface. The lumen and inter-tube gaps of the nanotubes confine the sodium deposition within the three-dimensional framework, constrain the volume expansion of sodium during deposition and dissolution, and avoid delamination and interface failure between the deposited layer and the substrate, thereby maintaining the stability of the current collector structure and the deposition interface during long-term cycling.

[0021] Thirdly, the three-dimensional sodium-loving current collector of this invention is prepared by a combination of anodic oxidation, cathodic reduction, and low-temperature heat treatment. The process is simple, the conditions are mild, and the controllability is strong, making it easy to achieve large-scale production and industrial promotion. Among them, the voltage, temperature, time, and electrolyte composition of anodic oxidation can control the length and diameter of the nanotubes; the current and time of cathodic reduction can control the type and concentration of introduced defects; and the low-temperature heat treatment stabilizes the introduced defects and inhibits their re-oxidation and deactivation without destroying the morphology of the nanotubes. The entire preparation process does not require complex equipment such as magnetron sputtering and chemical vapor deposition, is compatible with the existing metal foil production process, and the raw materials are readily available and the cost is low.

[0022] Fourth, the three-dimensional sodium-loving current collector of the present invention can be used as the negative electrode current collector of a negative electrode-free sodium battery. Uniform and reversible deposition and dissolution of sodium can be achieved without preloading negative electrode active materials, thereby improving the battery energy density while obtaining good cycle performance and coulombic efficiency.

[0023] Fifth, this invention achieves a balance between conductivity, sodium affinity, and three-dimensional structural stability on the same current collector through the synergistic design of a three-dimensional nanostructure layer, a defect control layer, and low-temperature heat treatment. The three-dimensional framework provides volume buffering and current equalization, the defect control layer simultaneously endows the current collector with excellent electronic conductivity and sodium affinity, and the low-temperature heat treatment ensures the stability of defects during battery service.

[0024] Sixth, the technical solution of the present invention has good universality. The conductive metal substrate can be selected from materials such as titanium foil, nickel foil, aluminum foil and copper foil. The material of the three-dimensional nanostructure layer can be metal oxide, metal nitride, metal oxynitride or metal sulfide. It can be flexibly designed according to the needs of different battery systems, and provides a general design idea for the development of current collectors for negative electrode-free sodium batteries and even other alkali metal batteries. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the structure of the three-dimensional sodium-loving current collector of the present invention; Figure 2 This is a schematic flowchart of the method for preparing the three-dimensional sodium-loving current collector of the present invention; Figure 3 The result obtained in Embodiment 1 of the present invention Scanning electron microscope images of nanotube arrays, where (a) is the top view of the surface, (b) is the cross-sectional morphology, (c) is the magnified local cross-sectional morphology, and (d) is the magnified local cross-sectional morphology from another angle; Figure 4 In Embodiment 1 of the present invention Mott-Schottky curves of nanotube arrays before and after cathode reduction; Figure 5 is the voltage-time curves for sodium nucleation and deposition of the pure titanium foil in Comparative Example 1 and the sodium-philic 3D current collector in Example 1 of the present invention, wherein (a) is the pure titanium foil, and (b) is the sodium-philic 3D current collector; Figure 6 is the results of galvanostatic cycling test of a coin-type half-cell using the sodium-philic 3D current collector of the present invention, wherein (a) is the voltage-time curve, and (b) is the curve of Coulombic efficiency varying with the number of cycles; Figure 7 is the cycle capacity retention rate and charge-discharge efficiency curves of a soft-pack full cell using the sodium-philic 3D current collector in Example 3 of the present invention; In the figure: 1 - conductive metal substrate; 2 - 3D nanotube array; 3 - defect regulation layer. DETAILED DESCRIPTION

[0026] To make the objectives, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below with reference to the examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention. Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents and the like used are all commercially available unless otherwise specified.

[0027] Example 1 This example provides a defect engineering regulated sodium-philic 3D current collector, and the preparation method thereof includes the following steps: S1. Anodic oxidation: A titanium foil with a thickness of 0.1 mm is ultrasonically cleaned sequentially with acetone, ethanol and deionized water and then dried with nitrogen to serve as an anode, a platinum electrode is used as a cathode, a mixed solution of ethylene glycol and water at a volume ratio of 99:1 is used as a solvent, and an organic electrolyte dissolved with 0.2 M and 5 mM is used as the electrolyte. Anodic oxidation is carried out at 25°C, the voltage is gradually reduced from 80 V to 5 V in a stepwise decreasing manner, and the oxidation time is about 2 h, so as to in-situ form on the surface of the titanium foil a nanotube array; S2. Cathodic reduction: the nanotube array obtained in S1 is used as a cathode, a platinum electrode is used as an anode, a 0.5 M aqueous sodium sulfate solution is used as an electrolyte, cathodic reduction treatment is carried out for 30 min at a current of 50 mA, so as to introduce oxygen vacancies and low-valence titanium ions into the nanotube array ( ), forming a non-stoichiometric , where 0<x<2; during the treatment process, the surface of the nanotube array gradually changes from off-white to blue, indicating that the aforementioned defects are successfully introduced.

[0028] S3. Low-temperature heat treatment: The product obtained in S2 is placed in a nitrogen atmosphere and heat-treated at 400℃ for 2 hours to obtain a three-dimensional sodium-loving current collector with defect engineering control.

[0029] Observed by scanning electron microscopy (see Figure 3 The results obtained in this embodiment The nanotubes in the nanotube array are approximately 15 μm long and 100 nm in diameter, and are aligned along the surface of the titanium foil. Mott-Schottky measurements were performed (see [link to Mott-Schottky analysis]). Figure 4 Before cathode reduction The donor concentration of the nanotube array is approximately 5.03 × 10⁻⁶. / After cathode reduction The donor concentration is approximately 1.04 × / This represents an increase of approximately four orders of magnitude.

[0030] Example 2 This embodiment uses secondary anodizing to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.05 mm thick titanium foil is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water, and then dried with nitrogen gas to serve as the anode. A platinum electrode is used as the cathode, and a mixture of ethylene glycol and water (volume ratio 98:2) is used as the solvent, containing 0.2 M... Using an organic electrolyte, the first layer is formed by anodic oxidation at 20°C for 60 minutes under constant voltage of 80V. After the first layer of nanotubes is removed by ultrasonic treatment, a second anodizing process is performed under the same conditions, with the voltage decreasing from 80V to 5V in a stepwise manner, forming a regularly arranged nanotube pattern in situ on the titanium foil surface. Nanotube arrays; S2, cathode reduction: obtained from S1 The nanotube array was used as the cathode and the platinum electrode as the anode. A 0.5M sodium sulfate aqueous solution was used as the electrolyte. The cathode was reduced at a current of 50mA for 30min to introduce oxygen vacancies and low-valence titanium ions. During the treatment, the surface of the nanotube array gradually changed from grayish-white to blue, indicating the successful introduction of the above-mentioned defects.

[0031] S3. Low-temperature heat treatment: The product obtained in S2 was placed in a nitrogen atmosphere and heat-treated at 350°C for 2 hours to obtain a three-dimensional sodium-loving current collector.

[0032] The results obtained in this embodiment were observed using a scanning electron microscope. The nanotube array is regularly arranged, with each nanotube having a length of approximately 20 μm and a diameter of approximately 110 nm.

[0033] Example 3 This embodiment prepares a three-dimensional sodium-loving current collector with a through-pore structure. The preparation method includes the following steps: S1. Anodizing: A 0.02 mm thick titanium foil is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water, and then dried with nitrogen gas to serve as the anode. A platinum electrode is used as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) is used as the solvent, containing 0.2 M... and 5mM An organic electrolyte was used as the electrolyte, and the titanium foil was continuously anodized at 80V at 5°C for 10 hours until it was completely oxidized, forming a porous structure. Nanotube array film; S2, cathode reduction: obtained from S1 The nanotube array film was used as the cathode and the platinum electrode as the anode. A 0.5M sodium sulfate aqueous solution was used as the electrolyte, and the cathode was reduced for 30 minutes at a current of 50mA. S3. Low-temperature heat treatment: The product obtained in S2 is placed in a nitrogen atmosphere and heat-treated at 400℃ for 2 hours to obtain a three-dimensional sodium-loving current collector with a through-pore structure.

[0034] The results obtained in this embodiment were observed using a scanning electron microscope. The nanotube array has a tube length of approximately 18 μm and a tube diameter of approximately 105 nm.

[0035] Example 4 This embodiment provides a three-dimensional sodium-loving current collector with defect engineering control, and the preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick titanium foil is used as the anode, a platinum electrode as the cathode, and a 90:10 volume ratio mixture of glycerol and water is used as the solvent, containing 0.1 M NaF and 3 mM... Using an organic electrolyte, anodizing was performed at 30°C with a constant voltage of 10V for 3 minutes, forming an in-situ layer on the titanium foil surface. Nanotube arrays; S2, cathode reduction: obtained from S1 The nanotube array was used as the cathode and the platinum electrode as the anode. A 0.5M sodium chloride aqueous solution was used as the electrolyte. The cathode was reduced at a current of 20mA for 60min to introduce oxygen vacancies and low-valence titanium ions. S3. Low-temperature heat treatment: The product obtained in S2 was placed in a nitrogen atmosphere and heat-treated at 300℃ for 3 hours to obtain a three-dimensional sodium-loving current collector.

[0036] The results obtained in this embodiment were observed using a scanning electron microscope. The nanotube array has a tube length of approximately 0.1 μm and a tube diameter of approximately 10 nm.

[0037] Example 5 This embodiment provides a three-dimensional sodium-loving current collector with defect engineering control, and the preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick titanium foil is used as the anode, a platinum electrode as the cathode, and a mixture of dimethyl sulfoxide and water (volume ratio 97:3) as the solvent, containing 0.5 M KF and 8 mM... An organic electrolyte was used as the electrolyte, and anodic oxidation was performed at 0°C. The voltage was gradually reduced from 300V to 5V in a stepwise manner, and the oxidation time was approximately 3 hours, resulting in in-situ formation of [a specific structure / product] on the titanium foil surface. Nanotube arrays; S2, cathode reduction: obtained from S1 The nanotube array was used as the cathode and the platinum electrode as the anode. A 0.5M sodium sulfate aqueous solution was used as the electrolyte. The cathode was reduced for 120 min at a current of 80 mA to introduce oxygen vacancies and low-valence titanium ions. S3. Low-temperature heat treatment: The product obtained in S2 was placed in an argon atmosphere and heat-treated at 450℃ for 1 hour to obtain a three-dimensional sodium-loving current collector.

[0038] The results obtained in this embodiment were observed using a scanning electron microscope. The nanotube array has a tube length of approximately 40 μm and a tube diameter of approximately 1000 nm.

[0039] Example 6 This embodiment uses titanium foil as a substrate to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick titanium foil is used as the anode, a platinum electrode as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) as the solvent, containing 0.3 M LiF and 5 mM... An organic electrolyte was used as the electrolyte, and anodic oxidation was performed at 25°C. The voltage was reduced from 100V to 5V in a linear manner, and the oxidation time was approximately 2 hours, resulting in in-situ formation of [a specific structure / product] on the titanium foil surface. Nanotube arrays; S2, cathode reduction: obtained from S1 The nanotube array is used as the cathode and the platinum electrode is used as the anode. The organic electrolyte described in S1 is used as the electrolyte. The cathode is reduced for 40 min at a current of 40 mA to introduce oxygen vacancies and low-valence titanium ions. S3. Low-temperature heat treatment: The product obtained in S2 was placed in a nitrogen atmosphere and heat-treated at 400℃ for 2 hours to obtain a three-dimensional sodium-loving current collector based on titanium foil.

[0040] The results obtained in this embodiment were observed using a scanning electron microscope. The nanotube array has a tube length of approximately 16 μm and a tube diameter of approximately 120 nm.

[0041] Example 7 This embodiment uses nickel foil as a substrate to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick nickel foil is used as the anode, a platinum electrode as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) as the solvent, containing 0.3 M... and 5mM The organic electrolyte is used as the electrolyte, and anodizing is carried out at 25°C. The voltage is reduced from 60V to 5V in an exponential manner, and the oxidation time is about 2 hours. A three-dimensional nanostructured nickel oxide layer is formed in situ on the surface of the nickel foil. S2, Cathodic Reduction: Using the three-dimensional nickel oxide nanostructure layer obtained in S1 as the cathode and the platinum electrode as the anode, and using 0.5M sodium sulfate aqueous solution as the electrolyte, the cathode was reduced for 40 min at a current of 40 mA to introduce oxygen vacancies and low-valence nickel ions into the nickel oxide to form a defect control layer. S3. Low-temperature heat treatment: The product obtained in S2 is placed in a nitrogen atmosphere and heat-treated at 350°C for 2 hours to obtain a three-dimensional sodium-loving current collector based on nickel foil.

[0042] Example 8 This embodiment uses aluminum foil as a substrate to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick aluminum foil is used as the anode, a platinum electrode as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) as the solvent, containing 0.3 M... The organic electrolyte is used as the electrolyte, and anodizing is carried out at 25°C. The voltage is reduced from 50V to 5V in a stepwise manner, and the oxidation time is about 2 hours. An aluminum oxide three-dimensional nanostructure layer is formed in situ on the surface of the aluminum foil. S2, Cathodic reduction: Using the three-dimensional nanostructured alumina layer obtained in S1 as the cathode and the platinum electrode as the anode, and 0.5M sodium sulfate aqueous solution as the electrolyte, the cathodic reduction was performed at a current of 40mA for 40min to introduce oxygen vacancies and low-valence aluminum ions. S3. Low-temperature heat treatment: The product obtained in S2 is placed in a nitrogen atmosphere and heat-treated at 400℃ for 2 hours to obtain a three-dimensional sodium-loving current collector with aluminum foil as the substrate.

[0043] Example 9 This embodiment uses aluminum foil as a substrate to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick aluminum foil is used as the anode, a platinum electrode as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) as the solvent, containing 0.3 M... and 5mM The organic electrolyte is used as the electrolyte. Anodizing is carried out at 25°C. The voltage is reduced from 60V to 5V in a stepwise manner. The oxidation time is about 2 hours. An aluminum oxide three-dimensional nanostructure layer is formed in situ on the surface of the aluminum foil. S2, Cathodic reduction: Using the three-dimensional nanostructure layer obtained in S1 as the cathode and the platinum electrode as the anode, and 0.5M sodium sulfate aqueous solution as the electrolyte, cathodic reduction was performed at a current of 40mA for 40min to introduce oxygen vacancies and low-valence metal ions. S3. Low-temperature heat treatment: The product obtained in S2 was placed in an argon atmosphere and heat-treated at 350°C for 2 hours to obtain a three-dimensional sodium-loving current collector based on aluminum foil.

[0044] Example 10 This embodiment uses copper foil as a substrate to prepare a three-dimensional sodium-loving current collector. The preparation method includes the following steps: S1. Anodizing: A 0.1 mm thick copper foil is used as the anode, a platinum electrode as the cathode, and a mixture of ethylene glycol and water (95:5 volume ratio) as the solvent, containing 0.3 M... The organic electrolyte is used as the electrolyte. Anodizing is carried out at 25°C. The voltage is reduced from 50V to 5V in a stepwise manner. The oxidation time is about 2 hours. A three-dimensional nanostructured copper oxide layer is formed in situ on the surface of the copper foil. S2, Cathodic Reduction: Using the three-dimensional copper oxide nanostructure layer obtained in S1 as the cathode and the platinum electrode as the anode, and 0.5M sodium sulfate aqueous solution as the electrolyte, the cathodic reduction was performed at a current of 40mA for 40min to introduce oxygen vacancies and low-valence copper ions. S3. Low-temperature heat treatment: The product obtained in S2 is placed in a nitrogen atmosphere and heat-treated at 300°C for 2 hours to obtain a three-dimensional sodium-loving current collector with copper foil as the substrate.

[0045] Example 11 This embodiment prepares a three-dimensional sodium-loving current collector with a metal oxynitride nanotube array as the three-dimensional nanostructure layer. Non-stoichiometric current collectors were prepared according to S1 to S3 of Example 1. After the nanotube array was formed, it was placed in an ammonia atmosphere and kept at 500°C for 1 hour for nitriding treatment. Nanotube arrays are converted into titanium oxynitrides ( Nanotube array. The resulting nanotube array maintains an oriented tubular morphology, and its tube walls contain a defect-modulating layer composed of oxygen vacancies, low-valence titanium ions, and lattice defects.

[0046] Example 12 This embodiment prepares a three-dimensional sodium-loving current collector with a metal nitride nanotube array as the three-dimensional nanostructure layer. It is prepared according to steps S1 to S3 of Example 1. After the nanotube array was formed, it was placed in an ammonia atmosphere and kept at 800℃ for 2 hours for deep nitriding, transforming the nanotube array into a titanium nitride nanotube array. The resulting titanium nitride nanotube array maintained an oriented tubular morphology and had good electronic conductivity. Its tube wall contained a defect control layer composed of low-valence titanium ions and lattice defects.

[0047] Example 13 This embodiment prepares a three-dimensional sodium-loving current collector with a metal sulfide nanotube array as the three-dimensional nanostructure layer. It is prepared according to steps S1 to S3 of Example 1. After the nanotube array is formed, it is placed together with sulfur powder in a tube furnace and subjected to sulfidation treatment at 400℃ for 2 hours under an argon atmosphere, so that the surface of the nanotube array is transformed into titanium sulfide. The resulting nanotube array maintains an oriented tubular morphology, and its tube walls contain a defect control layer composed of low-valence titanium ions and lattice defects.

[0048] Comparative Example 1 In this comparative example, untreated titanium foil was used as the current collector. A titanium foil with a thickness of 0.1 mm was taken, cleaned, dried and used directly as the current collector. No three-dimensional nanotube array was constructed on its surface, nor was a defect control layer introduced.

[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the S2 cathode reduction step is omitted. Specifically, a titanium foil with a thickness of 0.1 mm is taken and anodized according to S1 of Example 1 to form... After the nanotube array was formed, without cathodic reduction, it was directly heat-treated at 400°C for 2 hours in a nitrogen atmosphere according to S3 in Example 1, resulting in a product without the introduction of oxygen vacancies and low-valence titanium ion defects. Nanotube array current collector.

[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that the low-temperature heat treatment step S3 is omitted. That is, after performing anodic oxidation and cathodic reduction treatments sequentially according to S1 and S2 of Example 1, the low-temperature heat treatment is not performed, and the current collector is obtained directly.

[0051] Performance testing The current collectors obtained in Examples 1-13 and Comparative Examples 1-3 were subjected to the following performance tests: (1) Morphological characterization: The morphology, tube length, and tube diameter of the three-dimensional nanotube array on the current collector surface were observed using scanning electron microscopy (see [reference]). Figure 3 ).

[0052] (2) Carrier concentration characterization: The Mott-Schottky test was used to analyze the change in donor concentration of the three-dimensional nanotube array before and after cathode reduction, in order to characterize the introduction of oxygen vacancies and low-valence titanium ion defects and their effects on carrier concentration (see Figure 4 ).

[0053] (3) Button half-cell test: The current collector obtained in each embodiment or comparative example was used as the working electrode, and the sodium metal sheet was used as the counter electrode. 0.9M and 0.1M Using ethylene glycol dimethyl ether solution as the electrolyte and a ceramic-coated polypropylene membrane as the separator, a 2032 coin cell was assembled; at 1mA / Current density, 1mAh / Sodium deposition and dissolution tests were performed at the areal capacity, and the nucleation overpotential and deposition overpotential of sodium deposition were recorded (see [reference]). Figure 5 ), and tested the average coulombic efficiency during battery cycling (see Figure 6 ).

[0054] (4) Soft-pack full battery test: Sodium iron pyrophosphate, conductive carbon black and polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 8:1:1 to prepare a positive electrode slurry, which was coated on an aluminum foil with a thickness of 9 μm and dried under vacuum at 120°C for 12 h to obtain the positive electrode; the current collector obtained in each example or comparative example was used as the negative electrode current collector (the negative electrode side was not preloaded with negative electrode active material), and a ceramic-coated polypropylene separator was used to assemble a 1Ah soft-pack battery; charge-discharge cycle test was carried out at 25°C, 1C rate, and 1.5~3.4V voltage range, and the capacity retention rate and charge-discharge efficiency after 500 cycles were recorded (see Figure 7 ).

[0055] The test results of each embodiment and comparative example are shown in Table 1.

[0056] Table 1 Performance test results of each embodiment and comparative example Table 1 shows that in Comparative Example 1, the untreated titanium foil current collector had a nucleation overpotential of 128 mV, a deposition overpotential of 38 mV, an average coulombic efficiency of 95.5% for the half-cell, and a capacity retention of 51.0% after 500 cycles for the full cell. Comparative Example 2 only constructed [a process / treatment] on the surface of the titanium foil. The nanotube array without a defect control layer had a nucleation overpotential of 95 mV and a deposition overpotential of 25 mV, with a capacity retention of 68.0% after 500 full-cell cycles. Comparative Example 3 constructed a nanotube array and underwent cathode reduction, but without low-temperature heat treatment; its nucleation overpotential was 35 mV and its deposition overpotential was 5 mV, with a capacity retention of 73.0% after 500 full-cell cycles. Examples 1-13 constructed three-dimensional nanostructures with distributed defect control layers in situ on the surface of a conductive metal substrate. These layers had nucleation overpotentials of 28.5-50.0 mV and deposition overpotentials of 2.2-9.0 mV, achieving an average half-cell coulombic efficiency of over 99.77%, a capacity retention of 84.5-92.2% after 500 full-cell cycles, and a charge-discharge efficiency of over 99.7%.

[0057] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A three-dimensional sodium-loving current collector for defect engineering control, characterized in that, It includes a conductive metal substrate, a three-dimensional nanostructure layer constructed in situ on the surface of the conductive metal substrate, and a defect control layer distributed in the three-dimensional nanostructure layer; the defect control layer includes at least one of oxygen vacancies, low-valence metal ion defects, or lattice defects.

2. The three-dimensional sodium-loving current collector for defect engineering control according to claim 1, characterized in that, The conductive metal substrate is selected from one or more of titanium foil, nickel foil, aluminum foil, and copper foil.

3. The three-dimensional sodium-loving current collector for defect engineering control according to claim 1, characterized in that, The three-dimensional nanostructure layer is an array of nanotubes grown in situ on the surface of the conductive metal substrate, and the material of the nanotube array is selected from at least one of metal oxides, metal nitrides, metal oxynitrides and metal sulfides.

4. The three-dimensional sodium-loving current collector for defect engineering control according to claim 1, 2, or 3, characterized in that, The defect regulation layer includes oxygen vacancies and low-valence titanium ions, and the three-dimensional nanostructure layer is non-stoichiometric. Structure, where 0 <x<2。 5. A method for preparing a three-dimensional sodium-loving current collector with defect engineering control as described in claim 1, characterized in that, Includes the following steps: S1. Using the conductive metal substrate as the anode and the inert electrode as the cathode, anodic oxidation is performed in an organic electrolyte containing fluoride to form a three-dimensional nanotube array as the three-dimensional nanostructure layer in situ. S2. Using the three-dimensional nanotube array as the cathode and the inert electrode as the anode, a cathode reduction treatment is performed in an electrolyte containing electrolyte to introduce oxygen vacancies and low-valence metal ion defects, forming the defect regulation layer. S3. The product obtained in S2 is heat-treated under a protective atmosphere to obtain the three-dimensional sodium-loving current collector.

6. The preparation method according to claim 5, characterized in that, The organic electrolyte in S1 comprises an organic solvent and a fluoride, wherein the organic solvent is selected from one or more of ethylene glycol, glycerol, and dimethyl sulfoxide, and the fluoride is selected from... One or more of NaF, KF, and LiF, wherein the concentration of the fluoride in the organic electrolyte is 0.05~1M; the organic electrolyte also contains 1~10mM of [a specific compound / component]. .

7. The preparation method according to claim 5, characterized in that, The anodizing temperature described in S1 is 0~30℃, the voltage is 5~300V, and it is applied in a step-decreasing, linearly decreasing or exponentially decreasing manner. The anodizing is either a single anodizing or a double anodizing. The double anodizing is performed by removing the nanotube layer by ultrasound after the nanotubes are formed by the first anodizing, and then performing a second anodizing under the same conditions.

8. The preparation method according to claim 5, characterized in that, The electrolyte in S2 is a sodium sulfate solution, a sodium chloride solution, or an organic electrolyte; the current for the cathode reduction treatment is 1~100mA, and the time is 10min~2h.

9. The preparation method according to claim 5, characterized in that, The protective atmosphere described in S3 is nitrogen or argon, and the heat treatment temperature is 250~500℃ and the time is 0.5~5h.

10. A sodium battery without a negative electrode, characterized in that, It includes a positive electrode, a negative electrode current collector, an electrolyte, and a separator, wherein the negative electrode current collector is a three-dimensional sodium-loving current collector with defect engineering control as described in any one of claims 1 to 4, and the negative electrode current collector is not loaded with a negative electrode active material.